Devorando a história: midiatização, circulação e estratégias discursivas no canal Comer História - Stölben Junior, Paulo Antonio (2024)
This work aims to analyze the meanings woven by the discursive strategies produced around the "Comer História" channel. For this purpose, an initial investigation was conducted on Google Trends to understand the actions regarding recipe searches on Google and YouTube platforms. Historical recipe channels specifically on YouTube were then analyzed to define the object of analysis: the "Comer História" channel. The theoretical framework consists of authors discussing food, memory, and communication such as Jacob (2013), Espírito Santo Neto (2009), Halbwachs (1990), and Nora (1993). Concepts of mediatization, circulation of meanings, and discursive strategies are brought by Eliseo Verón (1985, 1996, 1997, 2004, 2007; 2008, 2013, 2014), Antônio Fausto Neto (2010a, 2010b, 2010c, 2016, 2018a, 2018b), and José Luiz Braga (2006, 2008, 2011, 2017). The methodology will be inspired by the socio-semiotics developed by Verón (1996, 2013) and the appropriation made by Fernández (2017, 2018, 2021). Four videos and three shorts are chosen for in-depth analysis. From this, clues about the discursive strategies produced by social actors are recognized (VERÓN, 1997; VERÓN; BOUTAUD, 2007) and then defined. The first strategy, called Spatial, stands out for the careful setting of the kitchen where the videos are recorded, establishing an atmosphere of closeness with the viewer. The second strategy, Descriptive, consists of a detailed description of the flavors of the dishes presented, aiming to compensate for the viewers' inability to taste them. The Didactic strategy complements the recipes with relevant historical information, contextualizing the dishes in the cultural and temporal landscape. The Exchange strategy is evidenced in the comments of the viewers, allowing the sharing of personal experiences and memories related to cuisine, contributing to the formation of a collective narrative around food. Finally, the Affluence strategy marks the gradual transition of the channel's production to other platforms, reflecting the complex dynamics of mediatization. The conclusions of this study highlight the interaction and complementarity of the discursive strategies used by the "Comer História" channel, showing how these strategies contribute to the production and circulation of meanings around food, history, and memory. Furthermore, the work points to the importance of considering different social, affective, and mediatic memories in the analysis of discursive strategies, as well as the possibility of expanding the scope of research to investigate more frequent strategies on other platforms, further enriching the understanding of the complexity of communication processes.